Strategic Planning Reality In The National Center For Gifted In Sport In Central and Southern Areas From Personnel's Point Of View - Abdul Wahid, Sgad (Journal of Physical Education, 2018)
The problem of the research lies in the lack of study for strategic planning of the national center for gifted in sports. The research aimed at identifying the strategic planning reality of the national center for gifted in sports. The researcher used the descriptive method. The subjects were (6) coaches and administrators in these centers from 31/1/2018 – 4/3/2018. The data was collected and treated using proper statistical operations to conclude that these centers need to pay more attention to forming their goals and strategic planning. In addition to that the researcher concluded that personnel should propose some ideas to form these goals, information and data collected should be more accurate to enable better strategic planning, all planning should be up to date and all limitations should be considered and managed. Finally the researcher recommended the necessity of including coaches and administrators in all level of strategic planning of the national center for gifted in sports and developing their abilities to execute these plans.